INTERPERSONAL VIOLENCE AGAINST ADOLESCENTS: AN ANALYSIS OF THE CASES NOTIFIED IN THE STATE OF ESPÍRITO SANTO - Thais França Armeláo Pereira; Dherik Fraga Santos; Mayara Alves Luis; Franciéle Marabotti Costa Leite (Universidade Federal do Paraná, 2023)
Objective: to identify the notification frequency of interpersonal violence against adolescents in Espírito Santo, Brazil, and its associated factors. Method: a cross-sectional study conducted with data from the Information System on Notifiable Health Problems from 2011 to 2018. The associations were tested by means of Pearson's chi-square test and Poisson regression. Results: the frequency of interpersonal violence was 72.2%. The outcome was associated with male adolescents, aged from 10 to 12 years old, of black/brown race/skin color, with no disabilities/disorders, occurrence on public roads, and male aggressors who were suspected of alcohol consumption (p<0.05). Conclusion: interpersonal violence is a problem with severe implications throughout life. This study helps to reveal the importance of surveilling violence in order to know the magnitude of the problem, as well as its characteristics for health promotion, prevention of the events and due intervention.